Shear wave velocity profile from microtremor surveys - Loo, Pooi Hieang (2018)
Microtremor survey method is a passive surface-wave test using vibrations from natural phenomena or human daily activities. The source is ubiquitous, weak, low frequencies vibrations. Due to the low frequencies, shear-wave velocity profile that are very deep can be obtained. In this report, microtremor (passive) sources as well as active-source data from the surface wave tests have been used to study the reliability of WAVe inversion method for the determination of Vs,30, the average shear wave velocity for the top 30m. WAVe is a newly developed inversion method proposed by Leong and Aung 2012. Twenty test sites representing varying dispersion trends and soil formations were digitized, following inversion analysis using WAVe method to obtain the shear-wave velocity profile of the soil. In addition, MASWaves inversion method, a recently available open source program, was also included for comparison. The results obtained are compared with those from advanced inversion methods reported for the test site, while invasive test measurements served as the benchmark for comparison of the shear wave velocity profile. In this report, a misfit function representing the gap between the observed (experimental) and the predicted (numerical) data was used for comparison. This study focuses on comparison between (1) theoretical and experimental dispersion curves, and (2) shear-wave velocity profile obtained from inversion analysis and invasive test measurement. Comparison of Vs,30 in seismic ground-type classification according to Eurocode 8 was further evaluated. From the study, it was shown that WAVe method has a better forward algorithm for the matching of experimental dispersion curve, it has the lowest misfit in most of the test sites compared to MASWaves and other inversion methods regardless of type of surface wave sources and mode of dispersion curve. However, the fitting of shear-wave velocity profiles with invasive test measurements are slightly poorer. Nevertheless, the inversion analysis from the different methods achieve comparable results, the determination of Vs,30 from different methods fall into the same seismic ground-type classification for most of the test sites.The results also underline that WAVe method tends to underestimate Vs,30 and MASWaves method tends to overestimate Vs,30 while other methods present a consistent linear trend when compared to the invasive test measurements. Hence, it can be concluded that WAVe method is a preferable solution for the application of seismic design of buildings due to slight conservatism in estimate of Vs,30. Overall, surface-wave methods have been shown to provide a robust and reliable estimation of Vs,30. Based on the studies, WAVe method can be regarded as a reliable inversion tool for the application of surface-wave tests.